2016
DOI: 10.1007/s00894-016-3150-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure and functional dynamics characterization of the ion channel of the human respiratory syncytial virus (hRSV) small hydrophobic protein (SH) transmembrane domain by combining molecular dynamics with excited normal modes

Abstract: The human respiratory syncytial virus (hRSV) is the major cause of lower respiratory tract infection in children and elderly people worldwide. Its genome encodes 11 proteins including SH protein, whose functions are not well known. Studies show that SH protein increases RSV virulence degree and permeability to small compounds, suggesting it is involved in the formation of ion channels. The knowledge of SH structure and function is fundamental for a better understanding of its infection mechanism. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…In vitro studies showed that SH inhibits apoptosis by blocking a tumor necrosis factor–mediated signaling pathway [ 19 ]. SH could thus promote viral replication by interfering with the host immune response and prolong viral replication in the host cell [ 20 ]. In preclinical studies in mice and cotton rats, SHe-vaccinated and intranasally challenged animals had reduced RSV replication, and SHe-specific antibodies were detected bound to the surface of RSV-infected cells [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that SH inhibits apoptosis by blocking a tumor necrosis factor–mediated signaling pathway [ 19 ]. SH could thus promote viral replication by interfering with the host immune response and prolong viral replication in the host cell [ 20 ]. In preclinical studies in mice and cotton rats, SHe-vaccinated and intranasally challenged animals had reduced RSV replication, and SHe-specific antibodies were detected bound to the surface of RSV-infected cells [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In group A strains, H51 (which is missing from RSV5–13) is a crucial residue in the regulation of SH ion channel activity [ 30 ]. Together with H22, H51 plays a key role in the opening and closing mechanism of the SH pentameric pore, since they are located in strategic places within the chains, close to the N- and C-termini [ 30 , 31 ]. An alternative amino acid at position 51 (Y, a non-basic amino acid) has been reported before, in a Brazilian GA5 strain from 2004 [ 28 ], but so far there were no reports of the deletion observed in RSV5–13.…”
Section: Discussionmentioning
confidence: 99%
“…One of these is targeting the third surface protein, the SH-protein, which most likely is involved in RSV pathogenicity rather than replication. 33 This novel mechanism is also the focus of vaccine investigations. 32 Other options continue to focus on the nucleocapsid.…”
Section: Preclinical Investigations and Future Directionsmentioning
confidence: 99%